BREAST CANCER IN VIEW OF AGE ASPECT IN ULYANOVSK REGION - A. A. Midlenko (Креативная хирургия и онкология)
The article presents an analysis of age-related characteristics of breast cancer  in the Ulyanovsk region. It says that  there  are more patients with age over 60 years has advanced stage of disease called “old” breast cancer patients and significantly  lower survival rate.